A high temperature resistant and thermal shock resistant amorphous oxide aerogel and its preparation method and application
By introducing hafnium oxide, rare earth oxide and silica into the oxide aerogel, the crystallization temperature is delayed, so that the aerogel remains amorphous in a high-temperature environment, solving the problem of degradation of thermal insulation performance of existing oxide aerogels at high temperatures, and achieving long-term service and high thermal insulation performance in high-temperature environments.
Patent Information
- Application Number
- CN202411183596.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-08-27
AI Technical Summary
Existing oxide aerogels are difficult to use for a long time in a temperature environment of 1000°C or higher, and are prone to sintering and phase change, resulting in degradation of thermal insulation performance or failure.
Multiple groups of aerogels are used, including hafnium oxide, rare earth oxide and silica. By regulating the volume ratio of alcohol and water and mixing after hydrolysis to form a sol, the crystallization temperature of hafnium oxide is delayed, so that the aerogel remains amorphous in a wide temperature range of 0 to 1050°C.
During the thermal shock cycle between 1050°C and room temperature, the aerogel can still maintain a specific surface area of more than 100m2/g, avoid volume changes caused by crystallization and phase transition, and achieve long-term service without failure.
Smart Images

Figure CN118978379B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and in particular relates to a high temperature resistant and thermal shock resistant amorphous oxide aerogel and a preparation method and application thereof. Background Art
[0002] With the development of aerospace technology, the concept of reusable launch vehicles has been proposed, and reusability has become a new direction for hypersonic aircraft. In the process of hypersonic reusable aircraft repeatedly performing missions, its thermal insulation materials not only withstand the high temperature caused by the aerodynamic heating effect, but also repeatedly experience thermal shock cycles from high temperature to normal temperature cooling in the atmospheric environment, which puts high demands on thermal insulation materials.
[0003] Oxide aerogel is an advanced thermal insulation material with low density, low thermal conductivity, high porosity, high specific surface area, and can be used for a long time in an aerobic environment. It is expected to meet the requirements of thermal insulation materials for hypersonic aircraft. However, common oxide aerogels are difficult to use for a long time in a temperature environment of 1000°C or higher: for example, silica aerogel will sinter at around 650°C, alumina aerogel will undergo a phase transition from spinel structure γ-Al2O3, θ-Al2O3, δ-Al2O3 to close-packed hexagonal structure α-Al2O3 at around 1000°C, and zirconium oxide will undergo a transformation from monoclinic phase to tetragonal phase at 1170°C. Sintering and phase change will produce a large volume change, causing the aerogel to shrink, pores to be destroyed, and specific surface area to decrease, resulting in a decrease in aerogel thermal insulation performance or failure.
[0004] By introducing heterogeneous elements into single-component aerogel to prevent the phase change and sintering of aerogel, the temperature resistance of aerogel has been improved to a certain extent. However, due to the limited temperature resistance limit of the main components and the volume change caused by high-temperature crystallization, it still affects its long-term service at high temperature. Summary of the invention
[0005] In order to solve the problem that the existing oxide aerogels cannot repeatedly and stably serve in a high-temperature environment, the present invention provides a high-temperature resistant and thermal shock resistant amorphous oxide aerogel and a preparation method and application thereof.
[0006] The technical solution of the present invention:
[0007] A high temperature resistant and thermal shock resistant amorphous oxide aerogel is a multi-component aerogel, the components of which include hafnium oxide, rare earth oxide and silicon dioxide, wherein the molar percentage of the component hafnium oxide is 50 mol%.
[0008] Furthermore, the molar percentage of the rare earth oxide is 10 to 40 mol%, and the molar percentage of the silicon dioxide is 10 to 40 mol%.
[0009] A method for preparing a high temperature resistant and thermal shock resistant amorphous oxide aerogel, the steps are as follows:
[0010] Step 1: Preparation of silica sol:
[0011] Mixing ethyl orthosilicate, deionized water and anhydrous ethanol in a molar ratio, adjusting the pH value of the obtained mixed system to 2 after stirring, and obtaining silica sol after stirring in a water bath;
[0012] Step 2: Preparation of mixed sol of hafnium and rare earth elements:
[0013] Adding a hafnium element precursor and a rare earth element precursor to a mixed solvent of deionized water and anhydrous ethanol, stirring in a water bath to obtain a mixed solution, adding glacial acetic acid to the mixed solution, stirring and cooling to room temperature, then adding epichlorohydrin, stirring for a certain period of time to obtain a mixed sol;
[0014] Step 3: Prepare gel:
[0015] Add the silica sol prepared in step 1 to the mixed sol prepared in step 2 according to the molar percentage of hafnium element of 50 mol%, and stir until gel a is formed;
[0016] Step 4: Aging treatment:
[0017] The gel a obtained in step 3 is soaked in anhydrous ethanol, and the anhydrous ethanol is replaced regularly for 3 times to obtain gel b; the gel b is soaked in an ethanol solution containing 20% Vol tetraethyl orthosilicate, and the ethanol solution containing tetraethyl orthosilicate is replaced regularly for 3 times to obtain gel c; the gel c is soaked in a dry solvent, and the dry solvent is replaced regularly for 3 times to obtain gel d;
[0018] Step 5: Drying:
[0019] The gel d obtained in step 4 is dried by supercritical drying or vacuum freeze drying to obtain a high temperature resistant and thermal shock resistant amorphous oxide aerogel.
[0020] Furthermore, in step 1, the molar ratio of ethyl orthosilicate, deionized water and anhydrous ethanol is 1:4:8; the stirring time is 30 minutes, and the reagent used for adjusting the pH value is dilute hydrochloric acid; the water bath stirring is stirring at 50° C. for 20 to 24 hours.
[0021] Furthermore, in step 2, the hafnium element precursor is one or a combination of hafnium tetrachloride, hafnium oxychloride, and hafnium oxynitrate, the rare earth element precursor is a rare earth element hexahydrate nitrate or hexahydrate chloride, and the rare earth element is one of yttrium, lanthanum, cerium, neodymium or gadolinium; and the concentration of the hafnium element precursor in the mixed solution is 10%wt.
[0022] Furthermore, in step 2, the volume ratio of deionized water to anhydrous ethanol is 1:10; the water bath stirring is stirring at 40-60° C. for 30 min; the added amounts of the glacial acetic acid and the epichlorohydrin are calculated based on the molar ratio of hafnium element, glacial acetic acid and epichlorohydrin of 1:1.5:4; the stirring condition after adding the glacial acetic acid is stirring at 40° C. for 30 min, and the stirring time after adding the epichlorohydrin is 5 min.
[0023] Furthermore, the immersion in step 4 is performed at a water bath temperature of 45° C., the timing is changed every 12 hours, and the drying solvent is anhydrous ethanol or tert-butanol.
[0024] Furthermore, the supercritical drying in step 5 is to place the gel d obtained in step 4 into a supercritical drying device, add anhydrous ethanol to soak the gel d, introduce nitrogen, maintain the pressure at 3.5 MPa, then increase the temperature to 273°C at a heating rate of 4°C / min, adjust the exhaust valve to maintain the pressure at 9 MPa, keep the temperature and pressure for 2 hours, and release the gas in the kettle to cool to room temperature.
[0025] Furthermore, the vacuum freeze drying in step 5 is to pre-freeze the gel d obtained in step 4 in a -20°C freezer for 12 hours, and then put it into a vacuum freeze drying device with a cold trap temperature of -50°C and a pressure of 10Pa, and vacuum freeze drying for 24 hours.
[0026] Application of high temperature resistant and thermal shock resistant amorphous oxide aerogel in reusable flight vehicles.
[0027] Furthermore, the application is to use the aerogel to prepare thermal insulation materials for hypersonic reusable aircraft.
[0028] Beneficial effects of the present invention:
[0029] The high temperature resistant and thermal shock resistant amorphous oxide aerogel provided by the present invention is a multi-component aerogel, which adopts hafnium oxide with high thermal stability and high phase transition temperature as the main component of the aerogel, and the modified and added items SiO2 and rare earth oxide are uniformly compounded with HfO2 through the liquid phase by adjusting the volume ratio of alcohol and water, and hydrolyzing them separately to form sols and then mixing them, thereby further improving the skeleton strength and the integrity of the macroscopic block, and quickly and stably obtaining an aerogel with low density, high specific surface area, low thermal conductivity and high temperature resistance.
[0030] The addition of heterogeneous elements delays the crystallization temperature of hafnium oxide, allowing the aerogel to remain amorphous in a wide temperature range of 0 to 1050°C, avoiding the impact of volume changes caused by crystallization and phase change on the micro-nano structure of the aerogel, and maintaining a porous structure in a high-temperature environment, allowing it to maintain a 100m after 15 30-min thermal shock cycles from 1050°C to room temperature. 2With a specific surface area of more than / g, it can achieve long-term service without failure and has good application prospects in reusable aircraft. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the element distribution diagram of the transmission electron image of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 1 after heat treatment at 1050°C / 30min;
[0032] Figure 2 This is a TEM image of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 1 after heat treatment at 900°C / 30min;
[0033] Figure 3 This is a TEM image of the hafnium oxide aerogel obtained in the comparative example after heat treatment at 900°C / 30min;
[0034] Figure 4 This is a graph showing the N2 adsorption and desorption curves of the high temperature and thermal shock resistant amorphous oxide aerogel obtained in Example 1 after 15 thermal shock cycles from 1050°C to room temperature;
[0035] Figure 5 This is a SEM picture of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 2;
[0036] Figure 6 This is the XRD picture of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 2 after heat treatment at 900°C / 30min;
[0037] Figure 7 This is the XRD image of the hafnium oxide aerogel obtained in the comparative example after heat treatment at 900°C / 30min;
[0038] Figure 8 This is a SEM image of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 3. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0040] Example 1
[0041] The present embodiment provides a high temperature resistant and thermal shock resistant amorphous oxide aerogel and a preparation method thereof.
[0042] The high temperature resistant and thermal shock resistant amorphous oxide aerogel of the present embodiment is a multi-component aerogel, the components of which include hafnium oxide, rare earth oxide and silicon dioxide, wherein the molar percentage of the component hafnium oxide is 50 mol%, the molar percentage of the rare earth oxide is 40 mol%, and the molar percentage of silicon dioxide is 10 mol%.
[0043] The preparation method of the high temperature resistant and thermal shock resistant amorphous oxide aerogel of this embodiment comprises the following steps:
[0044] Step 1: Preparation of silica sol:
[0045] Ethyl orthosilicate was mixed with deionized water and anhydrous ethanol in a molar ratio of 1:4:8 at room temperature, stirred for 30 minutes, and then diluted hydrochloric acid was added to adjust the pH to 2, and stirred in a water bath at 50°C for 24 hours to obtain silica sol;
[0046] Step 2: Preparation of mixed sol of hafnium and rare earth elements:
[0047] Weigh 50 mol% of hafnium element precursor hafnium tetrachloride and 40 mol% of rare earth element precursor yttrium nitrate hexahydrate in proportion, add hafnium tetrachloride and yttrium nitrate hexahydrate into a mixed solvent of deionized water and anhydrous ethanol in a volume ratio of 1:10, and stir in a water bath at 60° C. for 30 minutes to form a hafnium and yttrium mixed solution, in which the hafnium salt concentration is 10%wt.
[0048] Add glacial acetic acid to the obtained mixed solution at a molar ratio of HfCl4 to CH3COOH of 1:1.5, stir in a water bath at 40°C for 30 minutes, cool to room temperature, add epichlorohydrin to the mixed system cooled to room temperature at a molar ratio of HfCl4 to epichlorohydrin of 1:4, stir for 5 minutes and then hydrolyze to form a mixed sol of hafnium and yttrium;
[0049] Step 3: Prepare gel:
[0050] The silica sol prepared in step 1 is added to the mixed sol prepared in step 2 according to the molar percentage of hafnium element being 50 mol% and the molar percentage of silicon dioxide being 10 mol%, and stirred until gel a is formed;
[0051] Step 4: Aging treatment:
[0052] The gel a obtained in step 3 is immersed in anhydrous ethanol in a water bath at 45°C, and the anhydrous ethanol is replaced every 12 hours for 3 times to obtain gel b; the gel b is immersed in an ethanol solution containing 20% Vol tetraethyl orthosilicate in a water bath at 45°C, and the ethanol solution containing tetraethyl orthosilicate is replaced every 12 hours for 3 times to obtain gel c; the gel c is immersed in a dry solvent anhydrous ethanol in a water bath at 45°C, and the anhydrous ethanol is replaced every 12 hours for 3 times to obtain gel d;
[0053] Step 5: Drying:
[0054] The gel d obtained in step 4 is dried by supercritical drying, and the gel d obtained in step 4 is placed in a supercritical drying reactor, anhydrous ethanol is added to the reactor to soak the gel d, nitrogen is introduced to maintain a pressure of 3.5 MPa, and then the temperature is increased to a drying temperature of 273°C at a heating rate of 4°C / min, the exhaust valve is adjusted to maintain a pressure of 9 MPa, and the temperature is kept at this temperature for 2 hours. After the gas in the reactor is released and cooled to room temperature, a high-temperature resistant and thermal-shock resistant amorphous oxide aerogel is obtained.
[0055] The density of the high temperature resistant and thermal shock resistant amorphous oxide aerogel prepared in this embodiment is 0.21 g / cm 3 , the specific surface area is 323.12m 2 / g, and thermal conductivity is 0.036W / (m·K).
[0056] Example 2
[0057] The present embodiment provides a high temperature resistant and thermal shock resistant amorphous oxide aerogel and a preparation method thereof.
[0058] The high temperature resistant and thermal shock resistant amorphous oxide aerogel of the present embodiment is a multi-component aerogel, the components of which include hafnium oxide, rare earth oxide and silicon dioxide, wherein the molar percentage of the component hafnium oxide is 50 mol%, the molar percentage of the rare earth oxide is 40 mol%, and the molar percentage of silicon dioxide is 10 mol%.
[0059] The preparation method of the high temperature resistant and thermal shock resistant amorphous oxide aerogel of this embodiment comprises the following steps:
[0060] Step 1: Preparation of silica sol:
[0061] Ethyl orthosilicate was mixed with deionized water and anhydrous ethanol in a molar ratio of 1:4:8 at room temperature, stirred for 30 minutes, and then diluted hydrochloric acid was added to adjust the pH to 2, and stirred in a water bath at 50°C for 22 hours to obtain silica sol;
[0062] Step 2: Preparation of mixed sol of hafnium and rare earth elements:
[0063] Weigh 50 mol% of hafnium element precursor hafnium oxychloride and 40 mol% of rare earth element precursor yttrium chloride hexahydrate in proportion, add hafnium oxychloride and yttrium chloride hexahydrate into a mixed solvent of deionized water and anhydrous ethanol in a volume ratio of 1:10, and stir in a water bath at 40° C. for 30 minutes to form a hafnium and yttrium mixed solution, in which the hafnium salt concentration is 10%wt.
[0064] Add glacial acetic acid to the obtained mixed solution at a molar ratio of hafnium oxychloride to CH3COOH of 1:1.5, stir in a water bath at 40°C for 30 minutes, cool to room temperature, add epichlorohydrin to the mixed system cooled to room temperature at a molar ratio of hafnium oxychloride to epichlorohydrin of 1:4, stir for 5 minutes, and then hydrolyze to form a mixed sol of hafnium and yttrium;
[0065] Step 3: Prepare gel:
[0066] The silica sol prepared in step 1 is added to the mixed sol prepared in step 2 according to the molar percentage of hafnium element being 50 mol% and the molar percentage of silicon dioxide being 10 mol%, and stirred until gel a is formed;
[0067] Step 4: Aging treatment:
[0068] The gel a obtained in step 3 is immersed in anhydrous ethanol at 45°C in a water bath, and the anhydrous ethanol is replaced every 12 hours for 3 times to obtain gel b; the gel b is immersed in an ethanol solution containing 20% Vol tetraethyl orthosilicate at 45°C in a water bath, and the ethanol solution containing tetraethyl orthosilicate is replaced every 12 hours for 3 times to obtain gel c; the gel c is immersed in a dry solvent tert-butanol at 45°C in a water bath, and the tert-butanol is replaced every 12 hours for 3 times to obtain gel d;
[0069] Step 5: Drying:
[0070] The gel d obtained in step 4 was dried by vacuum freeze drying. The gel d obtained in step 4 was placed in a -20°C freezer for pre-freezing for 12 hours, and then placed in a vacuum freeze dryer with a cold trap temperature of -50°C and a pressure of 10Pa. After vacuum freeze drying for 24 hours, the high temperature resistant and thermal shock resistant amorphous oxide aerogel was obtained.
[0071] The density of the high temperature resistant and thermal shock resistant amorphous oxide aerogel prepared in this embodiment is 0.23 g / cm 3 , with a specific surface area of 300.65m 2 / g, and thermal conductivity is 0.038W / (m·K).
[0072] Example 3
[0073] The present embodiment provides a high temperature resistant and thermal shock resistant amorphous oxide aerogel and a preparation method thereof.
[0074] The high temperature resistant and thermal shock resistant amorphous oxide aerogel of the present embodiment is a multi-component aerogel, the components of which include hafnium oxide, rare earth oxide and silicon dioxide, wherein the molar percentage of the component hafnium oxide is 50 mol%, the molar percentage of the rare earth oxide is 10 mol%, and the molar percentage of silicon dioxide is 40 mol%.
[0075] The preparation method of the high temperature resistant and thermal shock resistant amorphous oxide aerogel of this embodiment comprises the following steps:
[0076] Step 1: Preparation of silica sol:
[0077] Ethyl orthosilicate was mixed with deionized water and anhydrous ethanol in a molar ratio of 1:4:8 at room temperature, stirred for 30 minutes, and then diluted hydrochloric acid was added to adjust the pH to 2, and stirred in a water bath at 50°C for 24 hours to obtain silica sol;
[0078] Step 2: Preparation of mixed sol of hafnium and rare earth elements:
[0079] 50 mol% of hafnium element precursor hafnium oxynitrate and 10 mol% of rare earth element precursor lanthanum nitrate hexahydrate were weighed in proportion, and hafnium oxynitrate and lanthanum nitrate hexahydrate were added to a mixed solvent of deionized water and anhydrous ethanol in a volume ratio of 1:10, and stirred in a water bath at 60° C. for 30 minutes to form a hafnium and lanthanum mixed solution, in which the hafnium salt concentration was 10%wt.
[0080] Add glacial acetic acid to the obtained mixed solution at a molar ratio of hafnium oxynitrate to CH3COOH of 1:1.5, stir in a water bath at 40°C for 30 minutes, cool to room temperature, add epichlorohydrin to the mixed system cooled to room temperature at a molar ratio of hafnium oxynitrate to epichlorohydrin of 1:4, stir for 5 minutes, and then hydrolyze to form a mixed sol of hafnium and lanthanum;
[0081] Step 3: Prepare gel:
[0082] The silica sol prepared in step 1 is added to the mixed sol prepared in step 2 according to the molar percentage of hafnium element being 50 mol% and the molar percentage of silicon dioxide being 40 mol%, and stirred until gel a is formed;
[0083] Step 4: Aging treatment:
[0084] The gel a obtained in step 3 is immersed in anhydrous ethanol in a water bath at 45°C, and the anhydrous ethanol is replaced every 12 hours for 3 times to obtain gel b; the gel b is immersed in an ethanol solution containing 20% Vol tetraethyl orthosilicate in a water bath at 45°C, and the ethanol solution containing tetraethyl orthosilicate is replaced every 12 hours for 3 times to obtain gel c; the gel c is immersed in a dry solvent anhydrous ethanol in a water bath at 45°C, and the anhydrous ethanol is replaced every 12 hours for 3 times to obtain gel d;
[0085] Step 5: Drying:
[0086] The gel d obtained in step 4 is dried by supercritical drying, and the gel d obtained in step 4 is placed in a supercritical drying reactor, anhydrous ethanol is added to the reactor to soak the gel d, nitrogen is introduced to maintain a pressure of 3.5 MPa, and then the temperature is increased to a drying temperature of 273°C at a heating rate of 4°C / min, the exhaust valve is adjusted to maintain a pressure of 9 MPa, and the temperature is kept at this temperature for 2 hours. After the gas in the reactor is released and cooled to room temperature, a high-temperature resistant and thermal-shock resistant amorphous oxide aerogel is obtained.
[0087] The density of the high temperature resistant and thermal shock resistant amorphous oxide aerogel prepared in this embodiment is 0.19 g / cm 3 , the specific surface area is 366.75m 2 / g, and thermal conductivity is 0.033W / (m·K).
[0088] Comparative Example 1
[0089] This comparative example provides a single-component hafnium oxide aerogel and a preparation method thereof.
[0090] The preparation method of the single-component hafnium oxide aerogel in this comparative example comprises the following steps:
[0091] Step 1: Prepare gel:
[0092] The hafnium element precursor hafnium tetrachloride was weighed and added into a mixed solvent of deionized water and anhydrous ethanol in a volume ratio of 1:10, and stirred in a water bath at 60° C. for 30 minutes to form a hafnium salt solution with a hafnium salt concentration of 10% wt.
[0093] Add glacial acetic acid to the obtained hafnium salt solution according to the molar ratio of HfCl4 to CH3COOH of 1:1.5, stir in a water bath at 40°C for 30 minutes, cool to room temperature, add epichlorohydrin to the mixed system cooled to room temperature according to the molar ratio of HfCl4 to epichlorohydrin of 1:4, stir for 5 minutes and hydrolyze to form gel a;
[0094] Step 2: Aging treatment:
[0095] The gel a obtained in step 1 is immersed in anhydrous ethanol in a water bath at 45°C, and the anhydrous ethanol is replaced every 12 hours for a total of 6 times to obtain gel b; the gel b is immersed in a dry solvent anhydrous ethanol in a water bath at 45°C, and the anhydrous ethanol is replaced every 12 hours for a total of 3 times to obtain gel c;
[0096] Step 3: Drying:
[0097] The gel c obtained in step 2 was dried by supercritical drying, and the gel c obtained in step 2 was placed in a supercritical drying reactor, anhydrous ethanol was added to the reactor to soak the gel c, nitrogen was introduced to maintain a pressure of 3.5 MPa, and then the temperature was increased to a drying temperature of 273°C at a heating rate of 4°C / min, the exhaust valve was adjusted to maintain a pressure of 9 MPa, and the temperature was kept at this temperature for 2 hours. After the gas in the reactor was released and cooled to room temperature, hafnium oxide aerogel was obtained.
[0098] The properties of the aerogels prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were tested, and the results were as follows:
[0099] Figure 1 The element distribution pictures of the transmission electron image of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 1 after heat treatment at 1050°C / 30min are respectively the HAADF image of the aerogel after heat treatment in Example 1, the Hf element surface scan of the aerogel after heat treatment in Example 1, the Si element surface scan of the aerogel after heat treatment in Example 1, and the Y element surface scan of the aerogel after heat treatment in Example 1. It can be seen from the figures that the aerogel still has the typical nanoscale pore structure of aerogel after high temperature heat treatment, and the distribution of each element therein is very uniform, indicating that the mixing after hydrolysis to form sol can effectively disperse each element uniformly;
[0100] Figure 2 This is a TEM picture of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 1 after heat treatment at 900°C / 30min. It can be seen that Example 1 still has a porous structure of less than 10nm after high temperature heat treatment, and the diffraction pattern is amorphous electron diffraction;
[0101] Figure 3 This is a TEM image of the hafnium oxide aerogel obtained in the comparative example after heat treatment at 900°C / 30min. It can be seen that the aerogel particles and pore size are significantly larger than those in Example 1, which reduces the thermal insulation performance of the aerogel. At the same time, obvious diffraction stripes and single crystal diffraction patterns can be seen.
[0102] Figure 2 and Figure 3 By comparison, it is easy to conclude that the present invention delays the crystallization temperature of aerogel by adding heterogeneous elements, avoids the influence of crystallization on the pore structure of aerogel during high-temperature heat treatment, and significantly improves the thermal insulation performance and service life of aerogel in high-temperature environment.
[0103] Figure 4 The N2 adsorption-desorption curves of the high temperature and thermal shock resistant amorphous oxide aerogel obtained in Example 1 after 15 1050°C to room temperature thermal shock cycles prove that the aerogel prepared in Example 1 still has a 100m 2 / g or more specific surface area, and has strong thermal shock resistance.
[0104] Figure 5 This is a SEM picture of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 2. Figure 8 This is a SEM picture of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 3. Figure 5 and Figure 8 It can be seen that the aerogels prepared by the method of the present invention all have a typical nanoscale porous structure of aerogels.
[0105] Figure 6 This is the XRD picture of the high temperature resistant and thermal shock resistant amorphous oxide aerogel obtained in Example 2 after heat treatment at 900°C / 30min. It can be seen that the aerogel still has an amorphous peak after high temperature heat treatment. Figure 7 This is the XRD image of the hafnium oxide aerogel obtained in the comparative example after heat treatment at 900°C / 30min. Obvious monoclinic HfO2 crystal characteristic diffraction peak can be seen, corresponding to PDF card 78-0050.
[0106] pass Figure 6 and Figure 7 The comparison further illustrates that the present invention delays the crystallization of hafnium oxide, allowing the aerogel to remain amorphous in a wide temperature range of 0 to 1050°C, and still maintain a porous structure in a high temperature environment, thereby avoiding the influence of crystallization on the pore structure of the aerogel and significantly improving the performance of the aerogel.
Claims
1. A high temperature resistant and thermal shock resistant amorphous oxide aerogel, characterized in that: The aerogel is a multi-component aerogel, and the components include hafnium oxide, rare earth oxide and silicon dioxide, wherein the molar percentage of the component hafnium oxide is 50 mol%, the molar percentage of the rare earth oxide is 10-40 mol%, and the molar percentage of the silicon dioxide is 10-40 mol%.
2. A method for preparing a high temperature resistant and thermal shock resistant amorphous oxide aerogel as claimed in claim 1, characterized in that: Here are the steps: Step 1: Preparation of silica sol: Mixing ethyl orthosilicate, deionized water and anhydrous ethanol in a molar ratio, adjusting the pH value of the obtained mixed system to 2 after stirring, and obtaining silica sol after stirring in a water bath; Step 2: Preparation of mixed sol of hafnium and rare earth elements: Adding a hafnium element precursor and a rare earth element precursor to a mixed solvent of deionized water and anhydrous ethanol, stirring in a water bath to obtain a mixed solution, adding glacial acetic acid to the mixed solution, stirring and cooling to room temperature, then adding epichlorohydrin, stirring for a certain period of time to obtain a mixed sol; Step 3: Prepare gel: Add the silica sol prepared in step 1 to the mixed sol prepared in step 2 at a molar percentage of hafnium element of 50 mol%, and stir until gel a is formed; Step 4: Aging treatment: The gel a obtained in step 3 is soaked in anhydrous ethanol, and the anhydrous ethanol is replaced regularly for 3 times to obtain gel b; the gel b is soaked in an ethanol solution containing 20% Vol tetraethyl orthosilicate, and the ethanol solution containing tetraethyl orthosilicate is replaced regularly for 3 times to obtain gel c; the gel c is soaked in a dry solvent, and the dry solvent is replaced regularly for 3 times to obtain gel d; Step 5: Drying: The gel d obtained in step 4 is dried by supercritical drying or vacuum freeze drying to obtain a high temperature resistant and thermal shock resistant amorphous oxide aerogel.
3. The method for preparing high temperature resistant and thermal shock resistant amorphous oxide aerogel according to claim 2, characterized in that: In step 1, the molar ratio of tetraethyl orthosilicate, deionized water and anhydrous ethanol is 1:4:8; the stirring time is 30 minutes, and the reagent used for adjusting the pH value is dilute hydrochloric acid; the water bath stirring is carried out at 50° C. for 20 to 24 hours.
4. The method for preparing high temperature resistant and thermal shock resistant amorphous oxide aerogel according to claim 3, characterized in that: In step 2, the hafnium element precursor is one or a combination of hafnium tetrachloride, hafnium oxychloride, and hafnium oxynitrate, the rare earth element precursor is a rare earth element hexahydrate nitrate or hexahydrate chloride, and the rare earth element is one of yttrium, lanthanum, cerium, neodymium, or gadolinium; the concentration of the hafnium element precursor in the mixed solution is 10%wt.
5. The method for preparing high temperature resistant and thermal shock resistant amorphous oxide aerogel according to claim 4, characterized in that: In step 2, the volume ratio of deionized water to anhydrous ethanol is 1:10; the water bath stirring is performed at 40-60° C. for 30 min; the amount of glacial acetic acid and epichlorohydrin added is calculated based on the molar ratio of hafnium element, glacial acetic acid and epichlorohydrin of 1:1.5:4; the stirring condition after adding glacial acetic acid is 40° C. for 30 min, and the stirring time after adding epichlorohydrin is 5 min.
6. The method for preparing high temperature resistant and thermal shock resistant amorphous oxide aerogel according to claim 5, characterized in that: The immersion in step 4 is carried out at a water bath temperature of 45° C., the timing is changed every 12 hours, and the drying solvent is anhydrous ethanol or tert-butanol.
7. The method for preparing high temperature resistant and thermal shock resistant amorphous oxide aerogel according to claim 6, characterized in that: The supercritical drying in step 5 is to put the gel d obtained in step 4 into a supercritical drying device, add anhydrous ethanol to soak the gel d, pass nitrogen, pass nitrogen to maintain the pressure at 3.5 MPa, then increase the temperature to 273°C at a heating rate of 4°C / min, adjust the exhaust valve to maintain the pressure at 9 MPa, keep the temperature and pressure for 2 hours, and release the gas in the kettle to cool to room temperature.
8. The method for preparing high temperature resistant and thermal shock resistant amorphous oxide aerogel according to claim 6, characterized in that: The vacuum freeze drying in step 5 is to pre-freeze the gel d obtained in step 4 in a -20°C freezer for 12 hours, and then put it into a vacuum freeze drying device with a cold trap temperature of -50°C and a pressure of 10Pa for vacuum freeze drying for 24 hours.
9. Use of the high temperature resistant and thermal shock resistant amorphous oxide aerogel as claimed in claim 1 in a reusable aircraft.
Citation Information
Patent Citations
In-situ composite silicon-based multibasic oxide oxide aerogel material and preparation method thereof
CN104941538A
Method for preparing germanium oxide and hafnium oxide hybrid aerogel composite
CN105777175A